Enzymatic esterification/transesterification of rice bran acid oil for subsequent γ-oryzanol recovery - Chonlatep Usaku; Asdarina Binti Yahya; Phannipha Daisuk; Artiwan Shotipruk (Biofuel Research Journal, 2023)
This study recovered γ-oryzanol from rice bran acid oil (RBAO), following an initial enzymatic esterification/transesterification to selectively convert its glyceride impurities into fatty acid ethyl esters (FAEEs) or biodiesel. γ-oryzanol was then deprotonated and separated from the biodiesel into the resulting aqueous phase via acid-base extraction. Herein, we determine the effects of varying reaction conditions, i.e., ethanol:RBAO molar ratio, temperature, reaction time, enzyme loading, and agitation speed, on the degrees of glyceride removal, γ-oryzanol loss, free fatty acid (FFA) remaining, and biodiesel content. Up to 100% glyceride removal was achieved with a relatively high biodiesel yield (84%) and γ-oryzanol loss as low as 26% under our most suitable reaction conditions (5:1 ethanol:RBAO molar ratio, 40 °C, 24 h reaction time, 10%wt enzyme loading, 200 rpm agitation). Furthermore, of the remaining oryzanol, up to 94% was recovered by the acid-base extraction with 2-4 M ethanolic NaOH solution. Our results suggest that a combination of enzymatic esterification/transesterification with subsequent acid-base extraction offers an efficient alternative approach to the simultaneous production of biodiesel and γ-oryzanol recovery from low-cost RBAO. Based on our analysis of techno-economic and environmental sustainability, integration of the present method into a rice bran oil refinery would make the process profitable, with the minimum use of toxic chemicals and energy.